Influence of rock matrix in kinetics oxidation for heavy oils - Trujillo- Portillo, Marta- Liliana (CT&F - Ciencia, Tecnología y Futuro, 2017)
This paper focuses on the study of the influence of rock matrix on oxidation kinetics through the analysis of kinetic experiments for a Colombian heavy crude using various porous media: synthetic sand, drilling cuttings, reservoir core and outcrop. The main objective is to evaluate the kinetic behavior of packing with porous media other than the original rock matrix to determine the feasibility of using them as a replacement for the original reservoir rock, while maintaining the representativeness of the results. The importance resides on the fact that the observed kinetics can be used to assess the technical feasibility for the implementation of an air injection process. The experimental design involves performing kinetic cell tests varying only the porous medium, while keeping the same fluid and the same operating conditions. For the dataset compiled, variables such as: oxygen consumed, carbon oxides produced and H/C ratio were determined. The results showed that it is possible to make reliable laboratory studies for air injection process using packing other than reservoir core as a more convenient alternative.